A Block by Block Method for Solving System of Volterra Integral Equations with Continuous and Abel Kernels - Katani, Roghayeh; Shahmorad, Sedaghat (Mathematical Modelling and Analysis, 2015)
The aim of the present paper is to introduce a block by block method for solving system of nonlinear Volterra integral equations with continuous kernels and system of Abel integral equations. We prove convergence of the method and show that its convergence order is at least six. To illustrate performance of the method, numerical experiments are presented and they are compared with HPM (Homotopy Perturbation Method) and RBFN (Radial Basis Function Network) method. The given results demonstrate remarkable ability of the proposed method.